Investigating vocabulary coverage and load in an Indonesian EFL textbook series - Rahmat, Yurieke Nadiya; Coxhead, Averil (Indonesian Journal of Applied Linguistics, 2021)
This article reports a corpus-based study of a series of Indonesian EFL textbooks for senior high school students from grades 10to 12 (16-18 years old), published by the Indonesian government. The textbooks were collected from the Indonesian bookkeeping information system and transferred into ready-to-analyse corpora using Range Programme (Heathley et al., 2002) to know the vocabulary load and what words are available for learning. The most significant finding in this study showed that the textbooks require 3,000-4,000 word families to reach 95% coverage with some help needed to comprehend the textbooks and 5,000-6,000 word families to gain 98% coverage which means the students can cope independently to read the textbooks. The textbooks contain a large amount of high-frequency words with more than 80% and up to 7% of Indonesian words which play roles in learning objectives and pre-vocabulary teaching activities. The results of this study suggest the vocabulary features and implications for learning, present the pedagogical implications for teachers and textbook writers, and provide a springboard for future research.